1991
DOI: 10.1152/jappl.1991.70.2.695
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone treatment in growth hormone-deficient adults. II. Effects on exercise performance

Abstract: Growth hormone (GH) treatment in adults with GH deficiency increases lean body mass and thigh muscle cross-sectional area. The functional significance of this was examined by incremental cycle ergometry in 24 GH-deficient adults treated in a double-blind placebo-controlled trial with recombinant DNA human GH (rhGH) for 6 mo (0.07 U/kg body wt daily). Compared with placebo, the rhGH group increased mean maximal O2 uptake (VO2max) (+406 +/- 71 vs. +133 +/- 84 ml/min; P = 0.016) and maximal power output (+24.6 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
188
4
6

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(212 citation statements)
references
References 0 publications
14
188
4
6
Order By: Relevance
“…Short-term placebo-controlled studies have demonstrated that GH replacement in adults improves diastolic (29) and systolic (30)(31)(32)(33) functions. The long-term effects of GH replacement on the heart have been investigated in a few open studies.…”
Section: The Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…Short-term placebo-controlled studies have demonstrated that GH replacement in adults improves diastolic (29) and systolic (30)(31)(32)(33) functions. The long-term effects of GH replacement on the heart have been investigated in a few open studies.…”
Section: The Heartmentioning
confidence: 99%
“…The standard incidence ratio (SIR) was calculated with a Swedish cohort of 138 000 of the general population above 18 years of age followed prospectively for 3 years as reference. explain the increased exercise capacity observed in some studies after GH replacement (30,(37)(38)(39)(40) including a recent meta-analysis of placebo-controlled, randomized GH treatment trials (41). However, if a too high dose of GH is given, there is a risk of inappropriate increment in left ventricular mass in elderly GHD adults during longterm treatment.…”
Section: The Heartmentioning
confidence: 99%
“…Adults with complete GH deficiency typically manifest a reduced lean body mass and muscle strength, an increased fat mass and a reduced exercise capacity (5,6). These abnormalities can be at least partially corrected by GH replacement (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological data suggest that adults with hypopituitarism have reduced life expectancy and a greater than two-fold increase in cardiovascular disease mortality when compared with healthy controls [24]. Moreover, various GH replacement trials in patients with GH deficiency consistently demonstrated increased LV function (LVEF) with somewhat inconsistent improvements in diastolic function, LV mass and exercise capacity [25][26][27][28].…”
Section: The Gh-igf Axis: Cardiac Issuesmentioning
confidence: 99%